2017
DOI: 10.1111/apa.13992
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus reuteri DSM 17938 and a placebo both significantly reduced symptoms in children with functional abdominal pain

Abstract: Both L. reuteri and the placebo were effective in alleviating pain in children with FAP, but only L. reuteri improved the child's and family's normal activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 28 publications
(36 reference statements)
0
31
0
1
Order By: Relevance
“…Although meta-analyses of paediatric trials have been performed, only few studies exist and with similar caveats to the adult meta-analyses 158,159 . Among five RCTs investigating children with FAP-NOS, the probiotic Lactobacillus reuteri DSM 1793 improved abdominal pain in three studies [160][161][162] , reduced functional disability but not abdominal pain in one study 163 , and was not superior to placebo in another 164 , although the methods of pain evaluation were different across studies. In children with IBS, two studies found that Lactobacillus rhamnosus GG was effective in reducing abdominal pain symptoms 165,166 and one study reported no improvement in abdominal pain but an improvement in perceived abdominal distention; measures of pain differed yet again among the different studies.…”
Section: Probioticsmentioning
confidence: 99%
“…Although meta-analyses of paediatric trials have been performed, only few studies exist and with similar caveats to the adult meta-analyses 158,159 . Among five RCTs investigating children with FAP-NOS, the probiotic Lactobacillus reuteri DSM 1793 improved abdominal pain in three studies [160][161][162] , reduced functional disability but not abdominal pain in one study 163 , and was not superior to placebo in another 164 , although the methods of pain evaluation were different across studies. In children with IBS, two studies found that Lactobacillus rhamnosus GG was effective in reducing abdominal pain symptoms 165,166 and one study reported no improvement in abdominal pain but an improvement in perceived abdominal distention; measures of pain differed yet again among the different studies.…”
Section: Probioticsmentioning
confidence: 99%
“…Jadrešin O et al [ 114 ] demonstrated that administration of L. reuteri DSM 17938 is associated with a reduction of the intensity and frequency of pain in population study including patients with FAP and IBS. Maragkoudaki M et al [ 115 ] found that in a paediatric cohort L. reuteri DSM 17938, at a dose of 2 X 10 8 CFU was not different from placebo in reducing the frequency and intensity of the abdominal pain episodes. By contrast in the intervention arm a reduction in pain relieving drugs was registered, even if not statistically significant.…”
Section: Resultsmentioning
confidence: 99%
“…Jadrešin et al 137 demonstrated a reduction in days with pain and pain severity in children with IBS and FAP. In studies focused specifically on FAP, Romano et al 138 reported reduced pain severity and Weizman et al 139 and Maragkoudaki et al 140 both reported reduced pain severity and frequency in those treated with the probiotic compared with placebo.…”
Section: Functional Gi Disordersmentioning
confidence: 99%